Revitalisasi Destinasi Wisata Bukit Kasih Kanonang melalui SWOT, TALC dan Green Accounting - P.E Porajow, Christine; Sony Erstiawan, Martinus; Tandaju, Teddy; Martono, Siswo (Majalah Ekonomi, 2026)
This study examines the revitalization strategy of Bukit Kasih Kanonang within the framework of the Tourism Area Life Cycle (TALC) by integrating SWOT analysis and Green Accounting. In recent years, the destination has experienced stagnating visitor growth, declining facility quality, and reduced competitiveness, raising concerns about its long term sustainability. The purpose of this research is to analyze the destination’s life cycle position, identify internal and external strategic factors, and formulate a rejuvenation model grounded in environmental accountability. The study employs a descriptive qualitative approach strengthened by strategic quantitative analysis. Data were collected through direct observation, visitor questionnaires based on the 4A components (attraction, accessibility, amenities, ancillary services), in-depth interviews with local stakeholders, and document analysis. IFAS and EFAS matrices were used to evaluate internal and external factors, while the SWOT framework was integrated with a Green Accounting perspective to simulate environmental cost allocation and sustainability reporting mechanisms. The findings indicate that the destination is in the stagnation phase tending toward early decline, characterized by strong spiritual and natural attractions but weakened supporting amenities and management systems. Although external opportunities such as the growing trend of religious tourism exist, limited managerial integration and the absence of environmental accounting reduce adaptive capacity. The study concludes that rejuvenation should be understood as a structural transformation toward sustainable governance, integrating ecological accountability, green facility revitalization, and strategic differentiation to enhance long term competitiveness.